Unclaimed Bodies: The Discourse Tracing of Thailand Management of Unclaimed Bodies - Leongpanyawong, Phakkanan; Soonthornpan, Satin; Ang, Nimid (Journal of Thai Ombudsman, 2024)
As Thailand's population structure shifts, issues surrounding the dead without caretakers, unclaimed bodies, are likely to increase in the future. This study examines Thailand's management of unclaimed persons and how it differs from that of other countries due to unique historical factors. Chinese foundations have monopolized the management of unclaimed persons in Thailand. The primary objective of this paper is to analyze the Thai state's definition and articulation of the issue of unclaimed bodies. Through the use of discourse tracing methods and the concept of the "Modernization of Death," the study evaluates state relations with unclaimed persons at the micro, meso, and macro levels. The findings reveal that the Thai state views unclaimed persons as part of public health management, while Chinese foundations, influenced by religious beliefs, have assumed the state's role and shaped societal norms surrounding unclaimed deaths. By allowing Chinese foundations to manage unclaimed persons, the state has effectively relieved itself of its obligations in this area, as observed in contemporary Thailand. Overall, the study underscores how historical factors shape the management of unclaimed persons and highlights the significant role of Chinese foundations in Thai society.